Modern Japanese Fiction and Its Traditions : an Introduction. - Rimer, J. Thomas (Princeton legacy library., 2014)
Thomas Rimer's book seeks to explain the background, structural principles, and development of pre-modem and modern Japanese fiction in a way that is comprehensive, methodical, and accessible to the general reader. Originally published in 1987. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of t.